Impact of Teaching Social Studies through Modern Technology - Ayesha Iqbal; Anjum Bano Kazmi (Al-Qanṭara, 2023)
Integrating technology in education is the need of modern times. But use of technology in curriculum is still a challenging task. There are many educational institutions which are using technology to teach different subjects but still there are many internal and external factors that effects or cause hindrance in integrating technology in curriculum. As there is lack of student’s interest and motivation in social studies use of technology can overcome these failures through integrating technology in educational organizations for such kind of subjects. Educational standard in Pakistan is not up to the levels of different developed countries and the same are with social studies subject. The motivation level of students even drops further when the content is taught through using traditional methods of teaching as lecture method or demonstration method. The subject of social studies is dull and boring for the students although this subject is very important for their lifelong learning. It helps students develop their problem-solving skills, critical thinking, and good citizenship. Unfortunately, the motivation strategies are used at higher education level for student’s better learning but on primary and elementary level these strategies seem to be missing. The purpose of choosing this topic is that the system is moving towards technology integration in all the subjects, but it should be observed that how much technology is important for the improvement of students learning process. Mostly teachers and students are hesitant of using technology, so the purpose of research was to make them find impact of using technology on teaching of Social Studies. To enhance student’s motivation and to impart better conceptual learning and to make the subject interesting for students’ researcher has applied technological techniques by making students do online homework in form of watching videos and solving quizzes to overcome traditional learning environment. The current study deals with the effectiveness of using technology in the subject of social studies through experimental design research. Students participated in this study in the month of September and October 2023. It was experimental designed research in which quantitative data was collected from students based on pre-test and post-test. The study consists of small sample size. Two classes with 30 students in each class were the part of this study in which Social Studies is a mandatory subject. In one class researcher used lecture method for teaching all topics and given regular homework while in other class researcher used lecture method in the class and for homework asked students to watch videos of related topics (uploaded on online portal Easyclass.com) and solve online quizzes. Purposive sampling has been used in this research due to convenience of the researcher. The technique has been adopted to keep uniformity of the subject matter and teaching method. Researcher recommends conducting future research with large sample size for the effective measurement of results. The data was analyzed through SPSS by using statistical techniques to examine the improvement in learning process with and without using technology. Relationship between variables was established through using Independent sample t-test with the help of SPSS version 23. A significant and positive connection determined by using technology in social studies is that it enhanced learning, motivation, and interest of students. It also directly affected student’s academic achievements.